Direct In Situ Vertical Growth of Interlaced Mesoporous NiO Nanosheets on Carbon Felt for Electrocatalytic Ammonia Synthesis. Issue 33 (4th May 2022) - Xiong, Wei; Zhou, Min; Huang, Xiaoyan; Yang, Weijie; Zhang, Da; Lv, Yaokang; Li, Hao
Abstract: Metal oxide nanomaterials directly grown on conductive substrates are optimal electrode materials because their structures allow for rapid ion and electron transport and thereby reduce internal resistance in the electrode. The development of such binder‐free, self‐supporting electrodes is of great significance for applications in electrocatalysis. In this work, a simple hydrothermal in situ self‐assembly reaction and annealing process was developed to prepare three kinds of nickel oxide @ carbon felt (NiO@CF) nanocomposites with different morphologies. The influence of different precipitators (strong or weak bases) on the morphology of the resulting nano‐sized nickel oxide nanocomposites was investigated. The microstructures of the NiO@CF samples were characterized with field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), X‐ray diffraction (XRD), and X‐ray photoelectron spectroscopy (XPS). When ammonia was used as the precipitator, NiO grew vertically on the surface of the carbon felt and formed a mesoporous nanosheet‐like structure (NiO NSs@CF). As an electrocatalytic nitrogen reduction reaction ( e ‐NRR) electrode, the NiO NSs@CF sample showed an excellent NH3 yield (71.3 μg h −1 mg −1 cat. ) and Faradaic efficiency (17.9 % at −0.5 V vs. RHE) in 0.1 M Na2 SO4 . The good performance was attributed to the vertical interleaved mesoporous sheet‐like structure (with the pore size of 15 nm and the thickness of ∼30 nm) and the relatively high concentration of oxygen vacancies. First‐principles calculations with strong on‐site Coulomb interactions demonstrated that the presence of oxygen vacancy on NiO sample leads to a significantly stronger N binding over the surface, benefiting for the nitrogen gas adsorption and reduction. The e ‐NRR performance of this binder‐free, flexible electrode material is superior to that of other reported nickel‐based nanomaterials. This study highlights the potential of such binder‐free carbon felt electrodes for use in e ‐NRR that could meet the needs of industrial production. Abstract : A novel interlaced mesoporous NiO NSs@CF electrochemical catalyst was prepared using a direct in situ vertical growth method, in which NiO formed mesoporous nanosheets with a pore size of 15 nm and a thickness of ∼30 nm. This binder‐free electrode exhibited a superior NH3 yield of 71.3 μg h −1 mg −1 cat. and a FE of 17.9 % at −0.5 V vs. RHE.